#1**+2 **

y=x+4 multiplied by 3 is 3y=3x+12. We can subtract the second equation from the first to get 0=5x+10. Then we solve for x.

0=5x+10

5x=-10

x=-2

Then we plug x=-2 into either of the equations to find y. y=x+4 will be simpler to work with so:

y=x+4

y=-2+4

y=2

Therefore** x=-2, y=2.**

gwenspooner85 Jul 13, 2020

#2**+1 **

Solve for the first variable in one of the equations, then substitute the result into the other equation.

Point Form:

(−2,2)

Equation Form:

x=−2,y=2

Hope this helps, whymenotsmart^m^.

whymenotsmart Jul 13, 2020